PROSOCIAL BEHAVIOUR AND ACADEMIC ACHIEVEMENT IN SPANISH STUDENTS OF COMPULSORY SECONDARY EDUCATION. - Inglés, Cándido; Benavides, Gemma; Redondo, Jesús; García-Fernández, José M.; Ruiz-Esteban, Cecilia; Estévez, Cordelia; Huescar, Elisa (Anales de Psicología / Annals of Psychology, 2009)
This study analyzed the prevelence of the prosocial behaviour and its relationship with two indexes of academic achievement, school records and repeating a school year, in a sample of 2022 Spanish students (51.1% boys) of compulsory secondary education. The prosocial behav-iour was measured with the Prosocial Behaviour scale of the Teenage Inventory of Social Skills (TISS). Results revealed that the proportion of prosocial students was 17.35%. The prosocial behaviour was significant and moder-ately more prevalent in girls than boys, finding a significant increase in grades 9 and 10 (d < .20). The proportion of prosocial students with all the approved subjects was significantly higher that the reported for the no-prosocial students group (d = .10). Likewise, the percentage of proso-cial students that repeat a school year was significantly smaller that the percentage found in the group of prosocial students that not repeat a school year (d = 2.43). Logistic regression analysis revealed that the proso-cial behaviour was a positive and statistically significant predictor of the academic success (OR = 1.01; 95% CI = 1.01-1.02), being the academic success, in turn, a positive and statistically significant predictor of the prosocial behaviour (OR = 1.44; 95% CI = 1.11-1.87).